Unraveling the Molecular Evolution of Blood Coagulation Genes in Fishes and Cetaceans - Mariz, João Pedro V.; Nery, Mariana F. (Frontiers in Marine Science, 2020)
Among the many physiological changes during the transition from an aquatic to a terrestrial lifestyle by early vertebrates, blood coagulation has an interesting history. The blood coagulation genes, originally composed of a single pathway in fishes, has expanded to include a second pathway in the evolution of the terrestrial vertebrates. However, genes of this second pathway have been secondarily lost in many lineages, as is the case of cetaceans, which returned to the aquatic environment along with their evolution. Here, we investigated the selective pressures on blood coagulation genes in a phylogenetic framework, focusing on fishes and cetaceans. Taking advantage of the availability of the genetic sequence for many vertebrate lineages and using a combination of bioinformatic tools, our results showed a diverse history of gene losses and gains, and with different selective pressure acting on different genes of blood coagulation functional pathway. Also, there was no evidence of a clear convergent molecular evolution between cetaceans and fishes, highlighting that there are many possible solutions found by evolution when it regards to a functional pathway that involves many genes.